Simulated space radiation exposure leads to long-term changes in molecular signatures of the heart - Mollie A. Brekker; Maya Semel; Ivan Korostenskij; Osanna Krikourian; Kaelyn M.W. Kelly; Julia Santos; Moniece Lowe; Siddhita Mhatre; Janani Iyer; Amber M. Paul; Stephanie Puukila; Joshua S. Alwood; et al. (Life Sciences in Space Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Lower but not upper thermal tolerance differs with opportunity for thermoregulation in a semi-fossorial lizard - David R. Tevs; Winsor H. Lowe (Journal of Thermal Biology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Recycling of ash particles during highly explosive eruptions: multiple glass populations in the 1.8 ka Taupō tephra - Simon J. Barker; Stephen B. Piva; Colin J. N. Wilson; David J. Lowe; Bruce L. A. Charlier; Alan R. Orpin (Bulletin of Volcanology, 2025)

Revisiting circular economy rebound: Market dynamics, policy implications, and future research directions - Benjamin H. Lowe; Andrea Genovese; David Font Vivanco; Trevor Zink (Journal of Industrial Ecology, 2025)
The circular economy has gained momentum as a sustainability paradigm that aims to decouple economic growth from environmental degradation by promoting resource efficiency and waste minimization. However, mounting evidence points to a critical challenge: circular economy rebound (CER). This phenomenon occurs when efficiency improvements intended to reduce resource use provoke systemic, market, or behavioral responses that diminish or even reverse the anticipated environmental gains. This is particularly problematic within growth‐oriented economies, where resource efficiency often reinforces rather than reduces consumption. This paper draws on insights from a roundtable discussion with leading experts—Trevor Zink, David Font Vivanco, and Andrea Genovese—to critically revisit the conceptual foundations of CER, assess the latest empirical evidence, and examine the policy and market dynamics shaping its occurrence. Rather than simply summarizing the discussion, the paper integrates these expert perspectives into a broader academic framework, offering an in‐depth analysis of unresolved questions such as the role of imperfect substitution, the systemic drivers of rebound, and the extent to which alternative economic models might mitigate its effects. Addressing CER, we argue, necessitates an interdisciplinary approach, combining insights from industrial ecology, behavioral economics, and political economy. Beyond technical solutions, it requires a reassessment of the broader economic structures underpinning growth‐oriented policies. The paper concludes by proposing a research and policy agenda that prioritizes robust quantification methods, interdisciplinary collaboration, and strategic interventions aimed at aligning circular economy initiatives with genuine sustainability goals.

Influence of minor β-CN genotypes on coagulation properties and proteolytic pathways of bovine milk - Nan Gai; Therese Uniacke-Lowe; David A. Goulding; Jonathan O'Regan; Michael Affolter; Alan L. Kelly (International Dairy Journal, 2025)

Unraveling recycling and climate influence on detrital U-Pb geochronology of titanite and apatite: An example from the Gaskiers Glaciation in Newfoundland - Nicolas Gómez; David Lowe; Sebastian Kommescher; Andrea Mills (Precambrian Research, 2025)

Carbonate cement genesis and links to siliciclastic environments of deposition: Hibernia Formation, Jeanne d’Arc basin, offshore Newfoundland - Mateo Acuna-Uribe; David Lowe; Karem Azmy (Marine and Petroleum Geology, 2025)

Reproductive strategy predicts thermal biology and microhabitat use in two lizards along a riparian-upland gradient - David R. Tevs; Winsor H. Lowe (Journal of Thermal Biology, 2025)

Using undrained cyclic triaxial tests to examine liquefaction resistance of historically liquefied pumiceous volcanic-ash soil materials and back-estimate prehistoric earthquakes - Jordanka Chaneva; Max O. Kluger; Ilanko Tehnuka; Vicki G. Moon; David J. Lowe; Rolando P. Orense (Engineering Geology, 2025)

Proteolytic pathways in bovine milk containing β-CN A1 or A2 - Nan Gai; Therese Uniacke-Lowe; Jonathan O'Regan; David A. Goulding; Michael Affolter; Christophe Fuerer; Alan L. Kelly (International Dairy Journal, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Influence of β-lactoglobulin and κ-casein genotype on whey protein denaturation in heated bovine milk and rennet whey - Nan Gai; Therese Uniacke-Lowe; Jonathan O'Regan; David A. Goulding; Alan L. Kelly (International Dairy Journal, 2025)

A framework for national-scale coastal storm hazards early warning - Ian L. Turner; Christopher K. Leaman; Mitchell D. Harley; Mandi C. Thran; Daniel R. David; Kristen D. Splinter; Nashwan Matheen; Jeff E. Hansen; Michael V.W. Cuttler; Diana J.M. Greenslade; Stefan Zieger; Ryan J. Lowe (Coastal Engineering, 2024)

Forecasting potential invaders to prevent future biological invasions worldwide - Arman N. Pili; Boris Leroy; John G. Measey; Jules E. Farquhar; Adam Toomes; Phillip Cassey; Sebastian Chekunov; Matthias Grenié; Dylan van Winkel; Lisa Maria; Mae Lowe L. Diesmos; Arvin C. Diesmos; et al. (Global Change Biology, 2024)
The ever‐increasing and expanding globalisation of trade and transport underpins the escalating global problem of biological invasions. Developing biosecurity infrastructures is crucial to anticipate and prevent the transport and introduction of invasive alien species. Still, robust and defensible forecasts of potential invaders are rare, especially for species without known invasion history. Here, we aim to support decision‐making by developing a quantitative invasion risk assessment tool based on invasion syndromes (i.e., generalising typical attributes of invasive alien species). We implemented a workflow based on ‘Multiple Imputation with Chain Equation’ to estimate invasion syndromes from imputed datasets of species' life‐history and ecological traits and macroecological patterns. Importantly, our models disentangle the factors explaining (i) transport and introduction and (ii) establishment. We showcase our tool by modelling the invasion syndromes of 466 amphibians and reptile species with invasion history. Then, we project these models to amphibians and reptiles worldwide (16,236 species [c.76% global coverage]) to identify species with a risk of being unintentionally transported and introduced, and risk of establishing alien populations. Our invasion syndrome models showed high predictive accuracy with a good balance between specificity and generality. Unintentionally transported and introduced species tend to be common and thrive well in human‐disturbed habitats. In contrast, those with established alien populations tend to be large‐sized, are habitat generalists, thrive well in human‐disturbed habitats, and have large native geographic ranges. We forecast that 160 amphibians and reptiles without known invasion history could be unintentionally transported and introduced in the future. Among them, 57 species have a high risk of establishing alien populations. Our reliable, reproducible, transferable, statistically robust and scientifically defensible quantitative invasion risk assessment tool is a significant new addition to the suite of decision‐support tools needed for developing a future‐proof preventative biosecurity globally.

Stratal evolution and provenance of a precambrian delta in a tectonically active terrane: The lower Signal Hill Group, Avalon Zone, Newfoundland - Santiago. Serna Ortiz; David G. Lowe (Precambrian Research, 2024)

Influence of β-casein genotype on Cheddar cheese making and ripening - Nan Gai; David S. Waldron; Therese Uniacke-Lowe; Bozhao Li; Jonathan O'Regan; David A. Goulding; Alan L. Kelly (International Dairy Journal, 2024)

Accelerating ocean species discovery and laying the foundations for the future of marine biodiversity research and monitoring - Alex David Rogers; Hannah Appiah-Madson; Jeff A. Ardron; Nicholas J. Bax; Punyasloke Bhadury; Angelika Brandt; Pier-Luigi Buttigieg; Olivier De Clerck; Claudia Delgado; Daniel L. Distel; Adrian Glover; Judith Gobin; et al. (Frontiers in Marine Science, 2023)
Ocean Census is a new Large-Scale Strategic Science Mission aimed at accelerating the discovery and description of marine species. This mission addresses the knowledge gap of the diversity and distribution of marine life whereby of an estimated 1 million to 2 million species of marine life between 75% to 90% remain undescribed to date. Without improved knowledge of marine biodiversity, tackling the decline and eventual extinction of many marine species will not be possible. The marine biota has evolved over 4 billion years and includes many branches of the tree of life that do not exist on land or in freshwater. Understanding what is in the ocean and where it lives is fundamental science, which is required to understand how the ocean works, the direct and indirect benefits it provides to society and how human impacts can be reduced and managed to ensure marine ecosystems remain healthy. We describe a strategy to accelerate the rate of ocean species discovery by: 1) employing consistent standards for digitisation of species data to broaden access to biodiversity knowledge and enabling cybertaxonomy; 2) establishing new working practices and adopting advanced technologies to accelerate taxonomy; 3) building the capacity of stakeholders to undertake taxonomic and biodiversity research and capacity development, especially targeted at low- and middle-income countries (LMICs) so they can better assess and manage life in their waters and contribute to global biodiversity knowledge; and 4) increasing observational coverage on dedicated expeditions. Ocean Census, is conceived as a global open network of scientists anchored by Biodiversity Centres in developed countries and LMICs. Through a collaborative approach, including co-production of science with LMICs, and by working with funding partners, Ocean Census will focus and grow current efforts to discover ocean life globally, and permanently transform our ability to document, describe and safeguard marine species.

Mobility and emplacement of an ancient, large-volume pyroclastic flow, Ongatiti Ignimbrite, North Island, New Zealand - Elham Yousef Zadeh; Adrian Pittari; David J. Lowe; Martin Danišík (Journal of Volcanology and Geothermal Research, 2023)

Long-term spatial variations in turbidity and temperature provide new insights into coral-algal states on extreme/marginal reefs - Paula J. Cartwright; Nicola K. Browne; David Belton; Iain Parnum; Michael O’Leary; Jurgen Valckenaere; Peter Fearns; Ryan Lowe (Coral Reefs, 2023)
Globally, coral reefs are under threat, with many exhibiting degradation or a shift towards algal-dominated regimes following marine heat waves, and other disturbance events. Marginal coral reefs existing under naturally extreme conditions, such as turbid water reefs, may be more resilient than their clear water counterparts as well as offer some insight into how reefs could look in the future under climate change. Here, we surveyed 27 benthic habitats across an environmental stress gradient in the Exmouth Gulf region of north Western Australia immediately following a marine heatwave event. We used multidecadal remotely sensed turbidity (from an in-situ validated dataset) and temperature, to assess how these environmental drivers influence variability in benthic communities and coral morphology. Long-term turbidity and temperature variability were associated with macroalgal colonisation when exceeding a combined threshold. Coral cover was strongly negatively associated with temperature variability, and positively associated with depth, and wave power, while coral morphology diversity was positively associated with turbidity. While moderate turbidity (long-term average ~ 2 mg/L suspended matter) appeared to raise the threshold for coral bleaching and macroalgal dominance, regions with higher temperature variability (> 3.5 °C) appeared to have already reached this threshold. The region with the least turbidity and temperature variability had the highest amount of coral bleaching from a recent heatwave event and moderate levels of both these variables may confer resilience to coral reefs.

Research priorities for the sustainability of coral-rich western Pacific seascapes - Graeme S. Cumming; Maja Adamska; Michele L. Barnes; Jon Barnett; David R. Bellwood; Joshua E. Cinner; Philippa J. Cohen; Jennifer M. Donelson; Katharina Fabricius; R. Quentin Grafton; Alana Grech; Georgina G. Gurney; et al. (Regional Environmental Change, 2023)
Nearly a billion people depend on tropical seascapes. The need to ensure sustainable use of these vital areas is recognised, as one of 17 policy commitments made by world leaders, in Sustainable Development Goal (SDG) 14 (‘Life below Water’) of the United Nations. SDG 14 seeks to secure marine sustainability by 2030. In a time of increasing social-ecological unpredictability and risk, scientists and policymakers working towards SDG 14 in the Asia–Pacific region need to know: (1) How are seascapes changing? (2) What can global society do about these changes? and (3) How can science and society together achieve sustainable seascape futures? Through a horizon scan, we identified nine emerging research priorities that clarify potential research contributions to marine sustainability in locations with high coral reef abundance. They include research on seascape geological and biological evolution and adaptation; elucidating drivers and mechanisms of change; understanding how seascape functions and services are produced, and how people depend on them; costs, benefits, and trade-offs to people in changing seascapes; improving seascape technologies and practices; learning to govern and manage seascapes for all; sustainable use, justice, and human well-being; bridging communities and epistemologies for innovative, equitable, and scale-crossing solutions; and informing resilient seascape futures through modelling and synthesis. Researchers can contribute to the sustainability of tropical seascapes by co-developing transdisciplinary understandings of people and ecosystems, emphasising the importance of equity and justice, and improving knowledge of key cross-scale and cross-level processes, feedbacks, and thresholds.

Monotonic and cyclic undrained behaviour and liquefaction resistance of pumiceous, non-plastic sandy silt - Jordanka Chaneva; Max O. Kluger; Vicki G. Moon; David J. Lowe; Rolando P. Orense (Soil Dynamics and Earthquake Engineering, 2023)

Seismically-induced down-sagging structures in tephra layers (tephra-seismites) preserved in lakes since 17.5 cal ka, Hamilton lowlands, New Zealand - Max O. Kluger; David J. Lowe; Vicki G. Moon; Jordanka Chaneva; Richard Johnston; Pilar Villamor; Tehnuka Ilanko; Richard A. Melchert; Rolando P. Orense; Remedy C. Loame; Nic Ross (Sedimentary Geology, 2023)

A novel method for identifying coded tags recorded on aquatic acoustic monitoring systems - Christopher D. Lowe; Nicolas J. C. Tregenza; Claudia J. Allen; Georgina E. Blow; Hanna Nuuttila; Chiara M. Bertelli; Anouska F. Mendzil; Thomas Stamp; Emma V. Sheehan; Peter Davies; Jonathan C. D. Gordon; Jonathan D. Bolland; et al. (Environmental Monitoring and Assessment, 2022)
Aquatic biotelemetry increasingly relies on using acoustic transmitters (‘tags’) that enable passive detection of tagged animals using fixed or mobile receivers. Both tracking methods are resource-limited, restricting the spatial area in which movements of highly mobile animals can be measured using proprietary detection systems. Transmissions from tags are recorded by underwater noise monitoring systems designed for other purposes, such as cetacean monitoring devices, which have been widely deployed in the marine environment; however, no tools currently exist to decode these detections, and thus valuable additional information on animal movements may be missed. Here, we describe simple hybrid methods, with potentially wide application, for obtaining information from otherwise unused data sources. The methods were developed using data from moored, acoustic cetacean detectors (C-PODs) and towed passive receiver arrays, often deployed to monitor the vocalisations of cetaceans, but any similarly formatted data source could be used. The method was applied to decode tag detections that were found to have come from two highly mobile fish species, bass ( Dicentrarchus labrax ) and Twaite shad ( Alosa fallax ), that had been tagged in other studies. Decoding results were validated using test tags; range testing data were used to demonstrate the relative efficiency of these receiver methods in detecting tags. This approach broadens the range of equipment from which acoustic tag detections can be decoded. Novel detections derived from the method could add significant value to past and present tracking studies at little additional cost, by providing new insights into the movement of mobile animals at sea.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Current carbon prices do not stack up to much land use change, despite bundled ecosystem service co‐benefits - David M. Summers; Courtney M. Regan; Claire Settre; Jeffery D. Connor; Patrick O’Connor; Hayley Abbott; Jacqueline Frizenschaf; Leon van der Linden; Andrew Lowe; Katja Hogendoorn; Scott Groom; Timothy R. Cavagnaro (Global Change Biology, 2021)
Biological sources of carbon sequestration such as revegetation have been highlighted as important avenues to combat climate change and meet global targets by the global community including the Paris Climate Agreement. However, current and projected carbon prices present a considerable barrier to broad‐scale adoption of tree planting as a key mitigation strategy. One avenue to provide additional economic and environmental incentives to encourage wider adoption of revegetation is the bundling or stacking of additional co‐beneficial ecosystem services that can be realized from tree planting. Using the World's largest land‐based carbon credit trading scheme, the Australian Emissions Reduction Scheme (ERF), we examine the potential for three pairs of ecosystem services, where the carbon sequestration value of land use change is paired with an additional co‐benefit with strong prospects for local tangible benefits to land owners/providers. Two cases consider agricultural provisioning values that can be realized by the landowners in higher returns: increased pollination services and reduced lamb mortality. The third case examined payments for tree plantings along riparian buffers, with payments to farmers by a water utility who realizes the benefit from reduced treatment cost due to water quality improvements. Economic incentives from these co‐benefit case studies were found to be mixed, with avoided treatment costs from water quality paired with carbon payments the most promising, while pollination and reduced lamb mortality paired with carbon payments were unable to bridge the economic gap except under the most optimistic assumptions. We conclude that the economics case for significant land use change are likely to be geographically dispersed and only viable in relatively niche landscape positions in high establishment, high opportunity cost areas even when carbon payments are augmented with the value of co‐benefits classified as providing direct and local benefits.

EMT-independent detection of circulating tumor cells in human blood samples and pre-clinical mouse models of metastasis - Jenna Kitz; David Goodale; Carl Postenka; Lori E. Lowes; Alison L. Allan (Clinical & Experimental Metastasis, 2021)
Circulating tumor cells (CTCs) present an opportunity to detect/monitor metastasis throughout disease progression. The CellSearch® is currently the only FDA-approved technology for CTC detection in patients. The main limitation of this system is its reliance on epithelial markers for CTC isolation/enumeration, which reduces its ability to detect more aggressive mesenchymal CTCs that are generated during metastasis via epithelial-to-mesenchymal transition (EMT). This Technical Note describes and validates two EMT-independent CTC analysis protocols; one for human samples using Parsortix® and one for mouse samples using VyCap. Parsortix® identifies significantly more mesenchymal human CTCs compared to the clinical CellSearch® test, and VyCap identifies significantly more CTCs compared to our mouse CellSearch® protocol regardless of EMT status. Recovery and downstream molecular characterization of CTCs is highly feasible using both Parsortix® and VyCap. The described CTC protocols can be used by investigators to study CTC generation, EMT and metastasis in both pre-clinical models and clinical samples.

Rainfall threshold for initiating effective stress decrease and failure in weathered tephra slopes - Max Oke Kluger; M. Ehsan Jorat; Vicki G. Moon; Stefan Kreiter; Willem P. de Lange; Tobias Mörz; Thomas Robertson; David J. Lowe (Landslides, 2020)

Crossing new frontiers: extending tephrochronology as a global geoscientific research tool - Peter M. Abbott; Britta J. L. Jensen; David J. Lowe; Takehiko Suzuki; Daniel Veres (Journal of Quaternary Science, 2020)

Source relationships between streambank soils and streambed sediments in a mercury-contaminated stream - Johnbull O. Dickson; Melanie A. Mayes; Scott C. Brooks; Tonia L. Mehlhorn; Kenneth A. Lowe; Jennifer K. Earles; Leroy Goñez-Rodriguez; David B. Watson; Mark J. Peterson (Journal of Soils and Sediments, 2019)

Subdividing the Holocene Series/Epoch: formalization of stages/ages and subseries/subepochs, and designation of GSSPs and auxiliary stratotypes - MIKE WALKER; Martin J. Head; John Lowe; Max Berkelhammer; Svante BjÖrck; Hai Cheng; Les C. Cwynar; David Fisher; Vasileios Gkinis; Antony Long; Rewi Newnham; Sune Olander Rasmussen; et al. (Journal of Quaternary Science, 2019)
The Holocene, which currently spans ~11 700 years, is the shortest series/epoch within the geological time scale (GTS), yet it contains a rich archive of evidence in stratigraphical contexts that are frequently continuous and often preserved at high levels of resolution. On 14 June 2018, the Executive Committee of the International Union of Geological Sciences formally ratified a proposal to subdivide the Holocene into three stages/ages, along with their equivalent subseries/subepochs, each anchored by a Global boundary Stratotype Section and Point (GSSP). The new stages are the Greenlandian (Lower/Early Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP2 ice core and dated at 11 700 a b2k (before 2000 CE); the Northgrippian (Middle Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP1 ice core and dated at 8236 a b2k; and the Meghalayan (Upper/Late Holocene Subseries/Subepoch) with its GSSP in a speleothem from Mawmluh Cave, north‐eastern India, with a date of 4250 a b2k. We explain the nomenclature of the new divisions, describe the procedures involved in the ratification process, designate auxiliary stratotypes to support the GSSPs and consider the implications of the subdivision for defining the Anthropocene as a new unit within the GTS.

Southern Ocean carbon-wind stress feedback - Ben Bronselaer; Laure Zanna; David R. Munday; Jason Lowe (Climate Dynamics, 2018)

HIV serology signal-to-cutoff ratio as a rapid method to predict confirmation of HIV infection - Lisa Li; David Puddicombe; Sylvie Champagne; Agatha Jassem; Mel Krajden; Linda Merrick; Christopher Lowe; Michael Payne (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

Metabolomics of tomato xylem sap during bacterial wilt reveals Ralstonia solanacearum produces abundant putrescine, a metabolite that accelerates wilt disease - Tiffany M. Lowe‐Power; Connor G. Hendrich; Edda von Roepenack‐Lahaye; Bin Li; Dousheng Wu; Raka Mitra; Beth L. Dalsing; Patrizia Ricca; Jacinth Naidoo; David Cook; Amy Jancewicz; Patrick Masson; et al. (Environmental Microbiology, 2018)
Summary Ralstonia solanacearum thrives in plant xylem vessels and causes bacterial wilt disease despite the low nutrient content of xylem sap. We found that R. solanacearum manipulates its host to increase nutrients in tomato xylem sap, enabling it to grow better in sap from infected plants than in sap from healthy plants. Untargeted GC/MS metabolomics identified 22 metabolites enriched in R. solanacearum ‐infected sap. Eight of these could serve as sole carbon or nitrogen sources for R. solanacearum . Putrescine, a polyamine that is not a sole carbon or nitrogen source for R. solanacearum , was enriched 76‐fold to 37 µM in R. solanacearum ‐infected sap. R. solanacearum synthesized putrescine via a SpeC ornithine decarboxylase. A Δ speC mutant required ≥ 15 µM exogenous putrescine to grow and could not grow alone in xylem even when plants were treated with putrescine. However, co‐inoculation with wildtype rescued ΔspeC growth, indicating R. solanacearum produced and exported putrescine to xylem sap. Intriguingly, treating plants with putrescine before inoculation accelerated wilt symptom development and R. solanacearum growth and systemic spread. Xylem putrescine concentration was unchanged in putrescine‐treated plants, so the exogenous putrescine likely accelerated disease indirectly by affecting host physiology. These results indicate that putrescine is a pathogen‐produced virulence metabolite.

No evidence for ecological segregation protecting native trout from invasive hybridization - Ryan P. Kovach; Clint C. Muhlfeld; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)

Legacy introductions and climatic variation explain spatiotemporal patterns of invasive hybridization in a native trout - Clint C. Muhlfeld; Ryan P. Kovach; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)
Hybridization between invasive and native species, a significant threat to worldwide biodiversity, is predicted to increase due to climate‐induced expansions of invasive species. Long‐term research and monitoring are crucial for understanding the ecological and evolutionary processes that modulate the effects of invasive species. Using a large, multidecade genetics dataset ( N = 582 sites, 12,878 individuals) with high‐resolution climate predictions and extensive stocking records, we evaluate the spatiotemporal dynamics of hybridization between native cutthroat trout and invasive rainbow trout, the world's most widely introduced invasive fish, across the Northern Rocky Mountains of the United States. Historical effects of stocking and contemporary patterns of climatic variation were strongly related to the spread of hybridization across space and time. The probability of occurrence, extent of, and temporal changes in hybridization increased at sites in close proximity to historical stocking locations with greater rainbow trout propagule pressure, warmer water temperatures, and lower spring precipitation. Although locations with warmer water temperatures were more prone to hybridization, cold sites were not protected from invasion; 58% of hybridized sites had cold mean summer water temperatures (

An assessment of the central disposition of intranasally administered insulin lispro in the cerebrospinal fluid of healthy volunteers and beagle dogs - Stephen Lowe; Emanuele Sher; Graham Wishart; Kimberley Jackson; Eunice Yuen; Claire Brittain; Siew Chinn Fong; David O. Clarke; William H. Landschulz (Drug Delivery and Translational Research, 2017)

A population PK model for citalopram and its major metabolite, N-desmethyl citalopram, in rats - Nieves Velez de Mendizabal; Kimberley Jackson; Brian Eastwood; Steven Swanson; David M. Bender; Stephen Lowe; Robert R. Bies (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Pollen–climate reconstruction from northern South Island, New Zealand (41°S), reveals varying high‐ and low‐latitude teleconnections over the last 16 000 years - Ignacio A. Jara; Rewi M. Newnham; Marcus J. Vandergoes; Courtney R. Foster; David J. Lowe; Janet M. Wilmshurst; Patricio I. Moreno; James A. Renwick; Aline M. Homes (Journal of Quaternary Science, 2015)
We present a 16 000‐year vegetation and climate reconstruction from pollen and plant macrofossil records obtained at a small alpine lake in South Island, New Zealand (41°S). The expansion of lowland forest taxa suggests a lifting of the altitudinal forest limits because of a warming pulse between 13 and 10k cal a BP and between 7 and 6k cal a BP, while their decline relative to upland forest taxa indicates cooling phases between 10 and 7k cal a BP and over the last 3000 years. The modern treeline was first established locally by 9.7k cal a BP. Forest persisted at the site until 3k cal a BP then disappeared from the record. Close correspondence between the temperature trends inferred from the pollen and macrofossil records and proxies from Antarctica and the Southern Ocean suggests a strong teleconnection between New Zealand and the Southern Hemisphere high‐latitudes between 15 and 6k cal a BP. We note that the breakdown of this coupling, a cooling trend in Adelaide Tarn and the local disappearance of beech forest after 3k cal a BP occur during a period of increased frequency of El Niño events, suggesting an enhanced teleconnection with the low‐latitudes during the late Holocene.

Climate association with fluctuation in annual abundance of fifty widely distributed moths in England and Wales: a citizen-science study - John Fawcett Wilson; David Baker; Mike Cook; George Davis; Roger Freestone; David Gardner; Dave Grundy; Norman Lowe; Steve Orridge; Heather Young (Journal of Insect Conservation, 2015)

Transient climate changes in a perturbed parameter ensemble of emissions-driven earth system model simulations - James M. Murphy; Ben B. B. Booth; Chris A. Boulton; Robin T. Clark; Glen R. Harris; Jason A. Lowe; David M. H. Sexton (Climate Dynamics, 2014)

Using palaeoenvironmental DNA to reconstruct past environments: progress and prospects - NICOLAS J. RAWLENCE; DAVID J. LOWE; JAMIE R. WOOD; JENNIFER M. YOUNG; G. JOCK CHURCHMAN; YU‐TUAN HUANG; ALAN COOPER (Journal of Quaternary Science, 2014)
Palaeoenvironmental DNA (PalEnDNA) is defined as ancient DNA (aDNA) originating from disseminated genetic material within palaeoenvironmental samples. Sources of PalEnDNA include marine and lake sediments, peat, loess, till, ice, permafrost, palaeosols, coprolites, preserved gut contents, dental calculus, tephras, and soils as well as deposits in caves/rockshelters and at archaeological sites. PalEnDNA analysis provides a relatively new tool for Quaternary and archaeological sciences and its applications have included palaeoenvironmental and palaeodietary reconstructions, testing hypotheses regarding megafaunal extinctions, human–environment interactions, taxonomic studies, and studies of DNA damage. Because PalEnDNA samples comprise markedly different materials, and represent wide‐ranging depositional and taphonomic contexts, various issues must be addressed to achieve robust, reproducible findings. Such issues include climatic and temporal limitations, the biological origin and state (free versus bound) of PalEnDNA, stratigraphic reliability, sterile sampling, ability to distinguish modern from aDNA signals, DNA damage and PCR amplification, DNA extraction methods, and taxonomic resolution. In this review, we provide a non‐specialist introduction to the use of PalEnDNA for Quaternary and archaeological researchers, assess attributes and limitations of this palaeoenvironmental tool, and discuss future prospects of using PalEnDNA to reconstruct past environments.

Lower Exposure and Faster Clearance of Bevacizumab in Gastric Cancer and the Impact of Patient Variables: Analysis of Individual Data from AVAGAST Phase III Trial - Kelong Han; Jin Jin; Mauricio Maia; John Lowe; Martina A. Sersch; David E. Allison (The AAPS Journal, 2014)

The alpha-7 nicotinic receptor partial agonist/5-HT3 antagonist RG3487 enhances cortical and hippocampal dopamine and acetylcholine release - Mei Huang; Anna R Felix; Sunoh Kwon; David Lowe; Tanya Wallace; Luca Santarelli; Herbert Y Meltzer (Psychopharmacology, 2014)

Long-term changes in bird community in the unmanaged post-fire eastern Québec boreal forest - Jeovanna Lowe; David Pothier; Ghislain Rompré; Jean-Pierre L. Savard (Journal of Ornithology, 2012)

ArxA, a new clade of arsenite oxidase within the DMSO reductase family of molybdenum oxidoreductases - Kamrun Zargar; Alison Conrad; David L. Bernick; Todd M. Lowe; Viktor Stolc; Shelley Hoeft; Ronald S. Oremland; John Stolz; Chad W. Saltikov (Environmental Microbiology, 2012)
Summary Arsenotrophy, growth coupled to autotrophic arsenite oxidation or arsenate respiratory reduction, occurs only in the prokaryotic domain of life. The enzymes responsible for arsenotrophy belong to distinct clades within the DMSO reductase family of molybdenum‐containing oxidoreductases: specifically arsenate respiratory reductase, ArrA, and arsenite oxidase, AioA (formerly referred to as AroA and AoxB). A new arsenite oxidase clade, ArxA, represented by the haloalkaliphilic bacterium Alkalilimnicola ehrlichii strain MLHE‐1 was also identified in the photosynthetic purple sulfur bacterium Ectothiorhodospira sp. strain PHS‐1. A draft genome sequence of PHS‐1 was completed and an arx operon similar to MLHE‐1 was identified. Gene expression studies showed that arxA was strongly induced with arsenite. Microbial ecology investigation led to the identification of additional arxA ‐like sequences in Mono Lake and Hot Creek sediments, both arsenic‐rich environments in California. Phylogenetic analyses placed these sequences as distinct members of the ArxA clade of arsenite oxidases. ArxA‐like sequences were also identified in metagenome sequences of several alkaline microbial mat environments of Yellowstone National Park hot springs. These results suggest that ArxA‐type arsenite oxidases appear to be widely distributed in the environment presenting an opportunity for further investigations of the contribution of Arx‐dependent arsenotrophy to the arsenic biogeochemical cycle.

Estrogen-related genes and their contribution to racial differences in breast cancer risk - Kerryn W. Reding; Chu Chen; Kimberly Lowe; David R. Doody; Christopher S. Carlson; Christina T. Chen; John Houck; Linda K. Weiss; Polly A. Marchbanks; Leslie Bernstein; Robert Spirtas; Jill A. McDonald; et al. (Cancer Causes & Control, 2012)

Effects of a novel mGlu2/3 receptor agonist prodrug, LY2140023 monohydrate, on central monoamine turnover as determined in human and rat cerebrospinal fluid - Stephen Lowe; Robert Dean; Bradley Ackermann; Kimberley Jackson; Fanni Natanegara; Shelby Anderson; James Eckstein; Eunice Yuen; Mosun Ayan-Oshodi; Mary Ho; David McKinzie; Kenneth Perry; et al. (Psychopharmacology, 2012)

Habitat and bathymetry influence the landscape‐scale distribution and abundance of drift macrophytes and associated invertebrates - Kevin H. Britton-Simmons; Alison L. Rhoades; Robert E. Pacunski; Aaron W. E. Galloway; Alexander T. Lowe; Elizabeth A. Sosik; Megan N. Dethier; David O. Duggins (Limnology and Oceanography, 2012)
We used a remotely operated vehicle to investigate landscape‐scale patterns of subtidal drift material and invertebrates within a 60‐km 2 marine basin in Washington State. Specifically, we quantified the distribution and abundance of drift macrophytes (seaweed and seagrass) and four macroinvertebrate species across depth and habitat type to depths of 170 m. Drift macrophytes were present on 97% of all video segments deeper than 30 m, with large drift piles particularly associated with low‐angle habitats at depths exceeding 70 m. Two commercially harvested species ( Strongylocentrotus franciscanus and Pandalus platyceros ) that feed directly on drift material appear to be distributed in space (depth and substrate type) so as to maximize access to drift macrophyte food resources, according to their respective feeding modes. Basin shape and depth drive the landscape‐scale distribution of drift material and indirectly the consumers that feed on it. The export of large amounts of detritus derived from nearshore macrophyte production into deep‐water habitats likely fuels extensive secondary production in these aphotic zones.

Field estimates of reproductive success in a model insect: behavioural surrogates are poor predictors of fitness - David J. Thompson; Christopher Hassall; Chris D. Lowe; Phillip C. Watts (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 905–913 Abstract Understanding, and therefore measuring, factors that determine fitness is a central problem in evolutionary biology. We studied a natural population of Coenagrion puella (Odonata: Zygoptera) over two entire breeding seasons, with over a thousand individuals uniquely marked and genotyped, and all mating events at the rendezvous site recorded. Using a parentage analysis, fitness of individuals in the first generation was quantified as the numbers of offspring that survived to maturity. Although mating behaviour can be predicted by environmental and demographical variables, the numbers of mature offspring produced (fitness) cannot, and crucially, are poorly correlated with behavioural observations of mating. While fitness of both sexes was positively related to mating behaviour and to female’s ectoparasite burden, these behavioural observations explained little more variance in offspring production than environmental and demographical variables. Thus, we demonstrate that behavioural measures of reproductive success are not necessarily reliable estimates of fitness in natural populations.

Immunological alterations mediated by adenosine during host-microbial interactions - Ioannis Drygiannakis; Peter B. Ernst; David Lowe; Ian J. Glomski (Immunologic Research, 2011)

Quaternary tephra marker beds and their potential for palaeoenvironmental reconstruction on Chatham Island, east of New Zealand, southwest Pacific Ocean - Katherine A. Holt; R. Clel Wallace; Vincent E. Neall; Barry P. Kohn; David J. Lowe (Journal of Quaternary Science, 2010)
Tephras provide one of the most reliable methods of time control and synchronisation within Quaternary sequences. We report on the identification of two widespread rhyolitic tephras – the Kawakawa and Rangitawa tephras – preserved in extensive peat deposits on Chatham Island ∼900 km east of New Zealand. The tephras, both products of supereruptions from the Taupo Volcanic Zone, occur as pale, fine‐ash dominated layers typically 10–150 mm thick. Mineralogically they are dominated by rhyolitic glass, together with subordinate amounts of quartz, feldspar, hypersthene, hornblende, Fe–Ti oxides and zircon. Phlogopite/biotite was identified additionally in Rangitawa Tephra. Ages for each tephra were obtained via mineralogical and major element glass composition‐based correlation with well‐dated equivalent deposits on mainland New Zealand, and we also obtained a new zircon fission‐track age for Rangitawa Tephra (350 ± 50 ka) on Chatham Island. Both tephras were erupted at critical times for palaeoenvironmental reconstructions in the New Zealand region: the Kawakawa at ca. 27 cal. ka, near the beginning of the ‘extended’ LGM early in marine isotope stage (MIS) 2; and the Rangitawa at ca. 350 ka near the end of MIS 10. The time constraints provided by the tephras demonstrate that Chatham Island peats contain long‐distance pollen derived from mainland New Zealand, which provides a reliable proxy for identifying glacial–interglacial climate conditions, in this case during the MIS 11–10 and MIS 2–1 cycles. The two tephras thus provide important chronostratigraphic tie‐points that facilitate correlation and synchronisation not only across the Quaternary deposits of the Chatham Islands group but also with climatically significant terrestrial and marine records in the wider New Zealand region. Copyright © 2010 John Wiley & Sons, Ltd.

The influence of seasonality on biomarker responses in Mytilus edulis - Josephine A. Hagger; David Lowe; Awantha Dissanayake; Malcolm B. Jones; Tamara S. Galloway (Ecotoxicology, 2010)

Testing Putative African Tropical Forest Refugia Using Chloroplast and Nuclear DNA Phylogeography - Andrew J. Lowe; David Harris; Eleanor Dormontt; Ian K. Dawson (Tropical Plant Biology, 2010)

Reproductive timing and patterns of development for the damselfly Coenagrion puella in the field - Chris D. Lowe; Ian F. Harvey; Phillip C. Watts; David J. Thompson (Ecology, 2009)
By a combination of detailed behavioral observations and molecular genetic approaches we have assessed development time, timing of first maturity, and the extent of genetic structure through the flying season in a wild population of the damselfly Coenagrion puella in England. This work provides the first estimate of development time (egg to mature adult) in the field based on individual damselflies. Development time was significantly longer for females than males. In contrast to reported laboratory studies, there was no difference in development times between different female color morphs. Development time ranged between 347 and 396 days and was negatively correlated with egg‐laying date. As a result eggs laid early in one season reach adult maturity relatively late in the next; concurrently individuals developing from eggs laid late mature relatively early. We speculate that this pattern of development is a direct physiological response to seasonal environmental variation and results in reproductive synchrony within a population. Size, specifically hind wing length, declined with development time in males, but not in females. In one of the two years of the study there was evidence for weak clustering of related individuals during the reproductive season. This appeared to be the result of developmental synchronization within families: variance in timing of maturation was smaller in full‐sib families than in half‐sib families or randomly assigned unrelated groups.

Climate change, conservation and management: an assessment of the peer-reviewed scientific journal literature - Adam Felton; Joern Fischer; David B. Lindenmayer; Rebecca Montague-Drake; Arianne R. Lowe; Debbie Saunders; Annika M. Felton; Will Steffen; Nicola T. Munro; Kara Youngentob; Jake Gillen; Phil Gibbons; et al. (Biodiversity and Conservation, 2009)

A landscape genetics approach for quantifying the relative influence of historic and contemporary habitat heterogeneity on the genetic connectivity of a rainforest bird - DAVID C. PAVLACKY JR; ANNE W. GOLDIZEN; PETER J. PRENTIS; JAMES A. NICHOLLS; ANDREW J. LOWE (Molecular Ecology, 2009)
Landscape genetics is an important framework for investigating the influence of spatial pattern on ecological process. Nevertheless, the standard analytic frameworks in landscape genetics have difficulty evaluating hypotheses about spatial processes in dynamic landscapes. We use a predictive hypothesis‐driven approach to quantify the relative contribution of historic and contemporary processes to genetic connectivity. By confronting genetic data with models of historic and contemporary landscapes, we identify dispersal processes operating in naturally heterogeneous and human‐altered systems. We demonstrate the approach using a case study of microsatellite polymorphism and indirect estimates of gene flow for a rainforest bird, the logrunner ( Orthonyx temminckii ). Of particular interest was how much information in the genetic data was attributable to processes occurring in the reconstructed historic landscape and contemporary human‐modified landscape. A linear mixed model was used to estimate appropriate sampling variance from nonindependent data and information‐theoretic model selection provided strength of evidence for alternative hypotheses. The contemporary landscape explained slightly more information in the genetic differentiation data than the historic landscape, and there was considerable evidence for a temporal shift in dispersal pattern. In contrast, migration rates estimated from genealogical information were primarily influenced by contemporary landscape change. We discovered that landscape heterogeneity facilitated gene flow before European settlement, but contemporary deforestation is rapidly becoming the most important barrier to logrunner dispersal.

Understanding uncertainty in future projections for the tropical Atlantic: relationships with the unforced climate - Peter Good; Jason A. Lowe; David P. Rowell (Climate Dynamics, 2009)

Formal definition and dating of the GSSP (Global Stratotype Section and Point) for the base of the Holocene using the Greenland NGRIP ice core, and selected auxiliary records - Mike Walker; Sigfus Johnsen; Sune Olander Rasmussen; Trevor Popp; Jørgen‐Peder Steffensen; Phil Gibbard; Wim Hoek; John Lowe; John Andrews; Svante Björck; Les C. Cwynar; Konrad Hughen; et al. (Journal of Quaternary Science, 2009)
The Greenland ice core from NorthGRIP (NGRIP) contains a proxy climate record across the Pleistocene–Holocene boundary of unprecedented clarity and resolution. Analysis of an array of physical and chemical parameters within the ice enables the base of the Holocene, as reflected in the first signs of climatic warming at the end of the Younger Dryas/Greenland Stadial 1 cold phase, to be located with a high degree of precision. This climatic event is most clearly reflected in an abrupt shift in deuterium excess values, accompanied by more gradual changes in δ 18 O, dust concentration, a range of chemical species, and annual layer thickness. A timescale based on multi‐parameter annual layer counting provides an age of 11 700 calendar yr b2 k (before AD 2000) for the base of the Holocene, with a maximum counting error of 99 yr. A proposal that an archived core from this unique sequence should constitute the Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period) has been ratified by the International Union of Geological Sciences. Five auxiliary stratotypes for the Pleistocene–Holocene boundary have also been recognised. Copyright © 2008 John Wiley & Sons, Ltd.

Reply to comment on “Deep groundwater flow and geochemical processes in limestone aquifers: evidence from thermal waters in Derbyshire, England, UK” by John Gunn, Simon H Bottrell, David J Lowe, Stephen R H Worthington. Hydrogeology Journal (2006), 14 (6), 868–881 - John Gunn; Simon H. Bottrell; David J. Lowe; Stephen R. H. Worthington (Hydrogeology Journal, 2008)

Strong genetic divergence indicates that congeneric damselflies Coenagrion puella and C. pulchellum (Odonata: Zygoptera: Coenagrionidae) do not hybridise - Chris D. Lowe; Ian F. Harvey; David J. Thompson; Phillip C. Watts (Hydrobiologia, 2008)

Structural basis for VO2+ inhibition of nitrogenase activity: (A) 31P and 23Na interactions with the metal at the nucleotide binding site of the nitrogenase Fe protein identified by ENDOR spectroscopy - Jan Petersen; Karl Fisher; David J. Lowe (JBIC Journal of Biological Inorganic Chemistry, 2008)

Structural basis for VO2+-inhibition of nitrogenase activity: (B) pH-sensitive inner-sphere rearrangements in the 1H-environment of the metal coordination site of the nitrogenase Fe–protein identified by ENDOR spectroscopy - Jan Petersen; Claire J. Mitchell; Karl Fisher; David J. Lowe (JBIC Journal of Biological Inorganic Chemistry, 2008)

Structural basis for VO2+ inhibition of nitrogenase activity (A): 31P and 23Na interactions with the metal at the nucleotide binding site of the nitrogenase Fe protein identified by ENDOR spectroscopy - Jan Petersen; Karl Fisher; David J. Lowe (JBIC Journal of Biological Inorganic Chemistry, 2008)

The demise of Arctic sea ice during stabilisation at high greenhouse gas concentrations - Jeff Ridley; Jason Lowe; David Simonin (Climate Dynamics, 2008)

Vegetation and climate of Auckland, New Zealand, since ca. 32 000 cal. yr ago: support for an extended LGM - Rewi M. Newnham; David J. Lowe; Teresa Giles; Brent V. Alloway (Journal of Quaternary Science, 2007)
Auckland occupies a climatically sensitive position close to a major biogeographic boundary in the southern mid‐latitudes. A new pollen record from Kohuora maar crater, Auckland, displays vegetation and climatic changes for the past ca. 32 000 years. Of particular interest are the inferred climatic patterns for the first part of the interval, encompassing the Last Glacial Maximum (LGM). The Kohuora record corresponds closely with pollen records from other Auckland sites indicating that the patterns observed are at least regional in extent. It is also broadly consistent with a variety of palaeoenvironmental evidence from across New Zealand, including the glacial record from Westland, other palynological records from North Island, other palaeoecological records from the South Island, and aeolian quartz sequences from western North Island. These records show that glacial conditions prevailed across most, if not all, of New Zealand during the interval ca. 29–19 k cal. yr BP, longer and earlier than the LGM sensu stricto . We suggest that the term extended LGM (eLGM) may be more appropriate for the New Zealand region. Within this predominantly cold interval, the Auckland pollen records indicate a climatic amelioration for the interval ca. 26–24 k cal. yr BP, also consistent with other palaeocological data from Canterbury, that fall within a period of climate amelioration recognised between the first two eLGM glacial advances in Westland. We refer to this warming interval as the eLGM Interstadial. The ca. 27 k cal. yr BP Kawakawa/Oruanui tephra is instrumental in most of these inter‐site comparisons and occurs after the first peak of eLGM cooling in a short‐lived comparatively mild phase. A subsequent return to apparently colder climate in the Auckland records may indicate a volcanic cooling effect or, more likely, widespread landscape disturbance following this major eruption event. Strong correspondence between biotic responses, glacial fluctuations and aeolian quartz deposition linked to major shifts in strength and latitudinal extent of the southern westerlies suggest that both the eLGM and eLGM Interstadial may be more widely registered, at least across the Southern Ocean. Support for this assertion comes from parallel investigations in western and southernmost South America and isotopic and palaeoecological records from Southern Ocean marine cores. Recent reconstructions of the globally averaged ice‐equivalent sea‐level history are in line with this evidence from the Southern Hemisphere, suggesting that the eLGM may have a global registration. In light of these observations, we suggest a re‐examination of the defined timing of the LGM along with renewed effort to establish climatic patterns during this period and understand their causes. Copyright © 2007 John Wiley & Sons, Ltd.

Test of AMS 14 C dating of pollen concentrates using tephrochronology - Rewi M. Newnham; Marcus J. Vandergoes; Mark H. Garnett; David J. Lowe; Christine Prior; Peter C. Almond (Journal of Quaternary Science, 2007)
Previous attempts to radiocarbon date sediments >10 kyr from the high rainfall region of Westland, New Zealand, a critical location for investigation of interhemispheric patterns of climate change, have been problematic. This study, building on recent work by Vandergoes and Prior ( 2003 ), shows that AMS 14 C dating of pollen concentrates has potential to provide more reliable ages than other sediment constituents, including plant macrofossils. The method was applied to sediments from three sites containing the 22.6k 14 C yr Kawakawa Tephra, which provided an independent test of the 14 C ages. Although some minor laboratory contamination was detected in tests on background standards, the modelled relationship between sample mass and measured 14 C content permitted an appropriate correction to be determined. Improved pollen concentrations derived by density separation between 1.4 and 1.2 specific gravity and sieving in the range 10–50 μm provided either older ages than other fractions of the same sample or, where in situ contamination was not evident, equivalent ages. Differences in degree of in situ contamination between depositional environments indicated that, in Westland, lake sites may be less susceptible to contamination by younger carbon than peat sites, where this process may be facilitated by root penetration into underlying sediments. Copyright © 2006 John Wiley & Sons, Ltd.

Towards a climate event stratigraphy for New Zealand over the past 30 000 years (NZ‐INTIMATE project) - Brent V. Alloway; David J. Lowe; David J. A. Barrell; Rewi M. Newnham; Peter C. Almond; Paul C. Augustinus; Nancy A. N. Bertler; Lionel Carter; Nicola J. Litchfield; Matt S. McGlone; Jamie Shulmeister; Marcus J. Vandergoes; et al. (Journal of Quaternary Science, 2007)
It is widely recognised that the acquisition of high‐resolution palaeoclimate records from southern mid‐latitude sites is essential for establishing a coherent picture of inter‐hemispheric climate change and for better understanding of the role of Antarctic climate dynamics in the global climate system. New Zealand is considered to be a sensitive monitor of climate change because it is one of a few sizeable landmasses in the Southern Hemisphere westerly circulation zone, a critical transition zone between subtropical and Antarctic influences. New Zealand has mountainous axial ranges that amplify the climate signals and, consequently, the environmental gradients are highly sensitive to subtle changes in atmospheric and oceanic conditions. Since 1995, INTIMATE has, through a series of international workshops, sought ways to improve procedures for establishing the precise ages of climate events, and to correlate them with high precision, for the last 30 000 calendar years. The NZ‐INTIMATE project commenced in late 2003, and has involved virtually the entire New Zealand palaeoclimate community. Its aim is to develop an event stratigraphy for the New Zealand region over the past 30 000 years, and to reconcile these events against the established climatostratigraphy of the last glacial cycle which has largely been developed from Northern Hemisphere records (e.g. Last Glacial Maximum (LGM), Termination I, Younger Dryas). An initial outcome of NZ‐INTIMATE has been the identification of a series of well‐dated, high‐resolution onshore and offshore proxy records from a variety of latitudes and elevations on a common calendar timescale from 30 000 cal. yr BP to the present day. High‐resolution records for the last glacial coldest period (LGCP) (including the LGM sensu stricto ) and last glacial–interglacial transition (LGIT) from Auckland maars, Kaipo and Otamangakau wetlands on eastern and central North Island, marine core MD97‐2121 east of southern North Island, speleothems on northwest South Island, Okarito wetland on southwestern South Island, are presented. Discontinuous (fragmentary) records comprising compilations of glacial sequences, fluvial sequences, loess accumulation, and aeolian quartz accumulation in an andesitic terrain are described. Comparisons with ice‐core records from Antarctica (EPICA Dome C) and Greenland (GISP2) are discussed. A major advantage immediately evident from these records apart from the speleothem record, is that they are linked precisely by one or more tephra layers. Based on these New Zealand terrestrial and marine records, a reasonably coherent, regionally applicable, sequence of climatically linked stratigraphic events over the past 30 000 cal. yr is emerging. Three major climate events are recognised: (1) LGCP beginning at ca. 28 000 cal. yr BP, ending at Termination I, ca. 18 000 cal. yr BP, and including a warmer and more variable phase between ca. 27 000 and 21 000 cal. yr BP, (2) LGIT between ca. 18 000 and 11 600 cal. yr BP, including a Lateglacial warm period from ca. 14 800 to 13 500 cal. yr BP and a Lateglacial climate reversal between ca. 13 500 and 11 600 cal. yr BP, and (3) Holocene interglacial conditions, with two phases of greatest warmth between ca. 11 600 and 10 800 cal. yr BP and from ca. 6 800 to 6 500 cal. yr BP. Some key boundaries coincide with volcanic tephras. Copyright © 2007 John Wiley & Sons, Ltd.

Deep groundwater flow and geochemical processes in limestone aquifers: evidence from thermal waters in Derbyshire, England, UK - John Gunn; Simon H. Bottrell; David J. Lowe; Stephen R. H. Worthington (Hydrogeology Journal, 2006)

Public Perceptions of Forest Management in North Central Arizona: The Paradox of Demanding More Involvement but Allowing Limits to Legal Action - David M. Ostergren; Kimberly A. Lowe; Jesse B. Abrams; Elizabeth J. Ruther (Journal of Forestry, 2006)
National-level forest policy is changing in response to social pressure to “improve forest health.” A particularly fierce public debate surrounds the forest health impacts of administrative appeals, lawsuits, public involvement, and federal agency ability to balance managerial efficiency, ecological health, and social expectations. A self-administered mail survey was conducted in 2003 to assess public opinion on litigation and forest restoration in north central Arizonan communities in the ponderosa pine ecosystem. Although results indicate some support for limits to the right to file suit, appeal, and review environmental decisions, an overwhelming number of respondents indicate a strong desire to be more informed and involved in forest management decisions.

Food habits and ontogenetic changes in the diet of the sandbar shark, Carcharhinus plumbeus, in Hawaii - W. David McElroy; Bradley M. Wetherbee; Carolyn S. Mostello; Christopher G. Lowe; Gerald L. Crow; Richard C. Wass (Environmental Biology of Fishes, 2006)

Prevalence of Whole-Body Skin Self-Examination in a Population at High Risk for Skin Cancer (Australia) - Joanne F. Aitken; Monika Janda; John B. Lowe; Mark Elwood; Ian T. Ring; Philippa H. Youl; David W. Firman (Cancer Causes & Control, 2004)

Tephrochronology of last termination sequences in Europe: a protocol for improved analytical precision and robust correlation procedures (a joint SCOTAV–INTIMATE proposal) - Chris S. M. Turney; J. John Lowe; Siwan M. Davies; Valerie Hall; David J. Lowe; Stefan Wastegård; Wim Z. Hoek; Brent Alloway (Journal of Quaternary Science, 2004)
The precise sequence of events during the Last Termination (18 000–9000 ka 14 C yr BP), and the extent to which major environmental changes were synchronous, are difficult to establish using the radiocarbon method alone because of serious distortions of the radiocarbon time‐scale, as well as the influences of site‐specific errors that can affect the materials dated. Attention has therefore turned to other methods that can provide independent tests of the chronology and correlation of events during the Last Termination. With emphasis on European sequences, we summarise here the potential of tephrostratigraphy and tephrochronology to fulfil this role. Recent advances in the detection and analysis of ‘hidden’ tephra layers (cryptotephra) indicate that some tephras of Last Termination age are much more widespread in Europe than appreciated hitherto, and a number of new tephra deposits have also been identified. There is much potential for developing an integrated tephrochronological framework for Europe, which can help to underpin the overall chronology of events during the Last Termination. For that potential to be realised, however, there needs to be a more systematic and robust analysis of tephra layers than has been the practice in the past. We propose a protocol for improving analytical and reporting procedures, as well as the establishment of a centralised data base of the results, which will provide an important geochronological tool to support a diverse range of stratigraphical studies, including opportunities to reassess volcanic hazards. Although aimed primarily at Europe, the protocol proposed here is of equal relevance to other regions and periods of interest. Copyright © 2004 John Wiley & Sons, Ltd.

Erratum - Daniel J. Becker; Jay T. Myers; Melissa M. Ruff; Peter L. Smith; Brenda W. Gillespie; David W. Ginsburg; John B. Lowe (Mammalian Genome, 2003)

Inbreeding and extinction: Effects of rate of inbreeding - David H. Reed; Edwin H. Lowe; David A. Briscoe; Richard Frankham (Conservation Genetics, 2003)

Chromosomal regions controlling resistance to gastro-intestinal nematode infections in mice - Fuad A. Iraqi; Jerzy M. Behnke; David M. Menge; Anna Lowe; Alan J. Teale; John P. Gibson; Leyden R. Baker; Derek Wakelin (Mammalian Genome, 2003)

Strain-specific modification of lethality in fucose-deficient mice - Daniel J. Becker; Jay T. Myers; Melissa M. Ruff; Peter L. Smith; Brenda W. Gillespie; David W. Ginsburg; John B. Lowe (Mammalian Genome, 2003)

Evidence for short-lived oscillations in the biological records from the sediments of Lago Albano (Central Italy) spanning the period ca. 28 to 17 k yr BP - Piero Guilizzoni; Aldo Marchetto; Andrea Lami; Frank Oldfield; Marina Manca; Claudio A. Belis; Anna M. Nocentini; Patrizia Comoli; Vivienne J. Jones; Steve Juggins; Christina Chondrogianni; Daniel Ariztegui; et al. (Journal of Paleolimnology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Receptor-specific ligands distinguish natriuretic peptide receptors-A and -C in primate tissues - Patricia Sehl; Jeff Y.K. Tom; David Oare; David G Lowe (Molecular and Cellular Biochemistry, 1998)

Cichlid spawning structures – bowers or nests? - Denis Tweddle; David H. Eccles; Clifford B. Frith; Geoffrey Fryer; Peter B.N. Jackson; Digby S.C. Lewis; Rosemary H. Lowe-McConnell (Environmental Biology of Fishes, 1998)

Stable carbon isotope variations in northwest Europe during the last glacial–interglacial transition - Chris S. M. Turney; David J. Beerling; Douglas D. Harkness; J. John Lowe; E. Marian Scott (Journal of Quaternary Science, 1997)

The metal-binding site of imidazole glycerol phosphate dehydratase; EPR and ENDOR studies of the oxo-vanadyl enzyme - J. Petersen; T. R. Hawkes; David J. Lowe (JBIC Journal of Biological Inorganic Chemistry, 1997)